2008
DOI: 10.1063/1.2993231
|View full text |Cite
|
Sign up to set email alerts
|

Tunable reflection minima of nanostructured antireflective surfaces

Abstract: Broadband antireflection schemes for silicon surfaces based on the moth-eye principle and comprising arrays of subwavelength-scale pillars are applicable to solar cells, photodetectors, and stealth technologies and can exhibit very low reflectances. We show that rigorous coupled wave analysis can be used to accurately model the intricate reflectance behavior of these surfaces and so can be used to explore the effects of variations in pillar height, period, and shape. Low reflectance regions are identified, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
195
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(205 citation statements)
references
References 16 publications
6
195
3
1
Order By: Relevance
“…The reflectance shows an oscillating behavior in the visible region, and the average reflectance decreases as the pitch increases from 200 to 350 nm. Similar successive maxima and minima in the reflectance spectrum are frequently observed from the moth-eye anti-reflection coatings [8][9][10][11]. The dependence of the reflectance maxima on the pitch is related to the interference by the two interfaces of the moth-eye layer [9].…”
Section: Simulationmentioning
confidence: 55%
See 2 more Smart Citations
“…The reflectance shows an oscillating behavior in the visible region, and the average reflectance decreases as the pitch increases from 200 to 350 nm. Similar successive maxima and minima in the reflectance spectrum are frequently observed from the moth-eye anti-reflection coatings [8][9][10][11]. The dependence of the reflectance maxima on the pitch is related to the interference by the two interfaces of the moth-eye layer [9].…”
Section: Simulationmentioning
confidence: 55%
“…In many moth-eye nanostructure cases, successive local maxima and minima are observed from the reflectance spectrum [8][9][10][11]. Their appearance is attributed to the thin-film interference and is known to be sensitive to the pitch of the array [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar low-reflection surfaces textured with arrays of nanopillars with different periods (pillar-to-pillar distance, from 150 nm to 350 nm), heights (from around 150 nm to 500 nm) and shapes (pillar width-to-period ratio from around 0.3 to 0.7) were fabricated by electron-beam lithography on silicon wafers [34]. In parallel, numerical simulations using the rigorous coupled-wave analysis (RCWA) indicated that as the height and shape of nanopillars as well as the array period affect reflectance, these parameters require optimization for best performance in the specific wavelength range over which the surface is required to function.…”
Section: Biomimeticsmentioning
confidence: 99%
“…Thin films exhibiting thickness-graded refractive index profiles are being intensively studied recently, for applications in antireflective coatings with enhanced omnidirectionality and broadband characteristics [4]. The refractive index profile and hence the reflection suppression, is controlled either by depositing layers of different materials or by controlling the in-depth void fraction variation using multiple deposition steps, by employing various types of lithography and subsequent pattern transfer such as plasma etching, by incorporating particles and properly tuned deposition processes etc [5][6][7][8][9][10][11]. Even though most of these coatings exhibit good AR performance, the scale-up and the integration of most of these processes are either difficult or subject to serious economic constraints.…”
Section: Introductionmentioning
confidence: 99%